Calculations of electron and positron scattering from vibrationally excited H2+ and H2 - Zammit, M.; Savage, J.; Fursa, Dmitry; Bray, Igor (2015)
© Published under licence by IOP Publishing Ltd. Electron and positron scattering from the vibrationally excited H2 + and H2 molecules were investigated using the adiabatic-nuclei convergent close-coupling method. Converged results are presented for a range of vibrationally excited states.